2019
DOI: 10.3389/fimmu.2019.01112
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity of Mesenchymal Stromal Cells: Finding the Right Route to Therapy

Abstract: Over the last decade, the acceleration in the clinical use of mesenchymal stromal cells (MSCs) has been nothing short of spectacular. Perhaps most surprising is how little we know about the “MSC product.” Although MSCs are being delivered to patients at an alarming rate, the regulatory requirements for MSC therapies (for example in terms of quality assurance and quality control) are nowhere near the expectations of traditional pharmaceuticals. That said, the standards that define a chemical compound or purifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 95 publications
3
82
0
Order By: Relevance
“…MSC-EVs exhibit most of the properties of MSCs and fundamental challenges relating to MSC heterogeneity affect biological properties and therapeutic potential of MSC-EVs, as well [103]. Differences in the proliferation rate, potential for multi-lineage differentiation and immunosuppressive properties of MSCs from different sources are well-documented [104]. Furthermore, even when MSCs were obtained from the same tissue of origin, they could have prodigious donor-to-donor variation in expression of membrane markers, transcriptional and proteomic profile [104].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSC-EVs exhibit most of the properties of MSCs and fundamental challenges relating to MSC heterogeneity affect biological properties and therapeutic potential of MSC-EVs, as well [103]. Differences in the proliferation rate, potential for multi-lineage differentiation and immunosuppressive properties of MSCs from different sources are well-documented [104]. Furthermore, even when MSCs were obtained from the same tissue of origin, they could have prodigious donor-to-donor variation in expression of membrane markers, transcriptional and proteomic profile [104].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the proliferation rate, potential for multi-lineage differentiation and immunosuppressive properties of MSCs from different sources are well-documented [104]. Furthermore, even when MSCs were obtained from the same tissue of origin, they could have prodigious donor-to-donor variation in expression of membrane markers, transcriptional and proteomic profile [104]. Aging also has a negative influence on self-renewal capacity, differentiation and immunosuppressive characteristics of MSCs, attenuating their therapeutic potential [105].…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical cord can be easily collected after birth and applied fresh, using the newborn's own, to treat tissue defects in autologous procedures (Živković, 1991;Sandler et al, 2004;Álvaro and Edwin, 2017). It can also be processed in order to obtain byproducts that are used in allogenic therapies Živković, 1991;Iftimia-Mander et al, 2013;Caputo et al, 2016;Wilson et al, 2019). Since the 1970s, it has been reported that HUC and its byproducts have great potential in the repair and regeneration of injured tissues.…”
Section: Previous Relevant Workmentioning
confidence: 99%
“…Large number of cells are required for identity verification, quality control, and expansion for grafting [156,157]. In addition, cellular heterogeneity and clonality have to be evaluated during scaled-up culturing [158]. It is anticipated that advances in cell sorting, expansion, and cultivation systems such as high-throughput bioreactors of various types [159] and closed adherent cell culture systems [157] will allow to overcome quality issues with time thus ensuring the safe use of MSCs in patients.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…It is anticipated that advances in cell sorting, expansion, and cultivation systems such as high-throughput bioreactors of various types [159] and closed adherent cell culture systems [157] will allow to overcome quality issues with time thus ensuring the safe use of MSCs in patients. This, of course, has to be accompanied by international regulatory framework adjustments for cell-based products manufacturing and use in trials and clinics [158]. Future effort will be aimed at establishing efficient and safe large-scale cell expansion protocols and harmonization of the regulatory issues related to clinical use of MSCs in regenerative medicine procedures such as tissue grafts.…”
Section: Future Perspectivesmentioning
confidence: 99%